Operationalizing Social Work Science Through Research–Practice Partnerships: Lessons From Implementation Science. (March 2017) - Palinkas, Lawrence A.; He, Amy S.; Choy-Brown, Mimi; Hertel, Amy Locklear
Recent efforts to identify and promote a distinct science for the discipline of social work have led to an ongoing debate regarding the nature and function of such a science. Central to this debate is a lack of consensus as to how to operationalize a social work science. Drawing from the field of implementation science and its application in reducing the gap between research and practice in child welfare and child mental health, this article examines the role of research–practice partnerships in creating and advancing social work science. Through the exercise of cultural exchanges among researchers, practitioners, policy makers, and other stakeholders, such partnerships offer the potential to integrate different disciplinary approaches to understanding why populations experience inequity or disadvantage and what to do about it as well as different perspectives on the nature and use of research evidence to achieve such understanding.